A Corotational Formulation For Geometrically Nonlinear Dynamics of 2D Flexible Beams - Andria, Novi; Zuhal, Lavi Rizki; Muhammad, Hari; Gunawan, Leonardo (Indonesian Journal of Aerospace, 2024)
A simple and efficient 2D corotational formulation for dynamic analysis of geometrically nonlinear flexible beam is presented in this paper. The corotational approach can easily facilitate the evaluation of internal elactic forces by introducing an element frame to separate rigid body motion and the deformational part. In the present study, the Euler-Bernoulli beam models with simple geometric stiffness matrix is employed and Newmark’s implicit time-stepping scheme with iterative predictor-corrector algorithm is adopted. The validity and efficiency of the present corotational formulation are verified by simulating three numerical examples. Despite its simple numerical implementation, simulation results confirms that the proposed formulation is highly accurate and efficient in simulating flexible beams undergoing large deformation.